'I don't understand it': first in family graduates recognising and mobilising capitals for employment. Issue 3 (3rd April 2022) - Groves, Olivia; O'Shea, Sarah; Delahunty, Janine
ABSTRACT: Success in a complex labour market requires astute planning, preparation and foresight, particularly within the context of the massification of higher education, increasing graduate competitiveness, and a discourse of employability which places the onus of employment on the individual. A cohort experiencing noticeably weaker graduate employment outcomes are students who are the first in their family to attend university, a group often representing a diversity of backgrounds and intersecting equity categories. Drawing on interviews and surveys of near completing Australian first in family (FiF) students, recent graduates and alumni, this article explores how employability was experienced and enacted by participants. Through the application of Pierre Bourdieu's work on capital theory, the article contributes valuable insights into the experience of FiF students' graduate employment seeking, specifically how their existing capitals, including those that are social, cultural and symbolic in nature, interacted with the job market to achieve (or otherwise) desirable graduate employment. Findings from this study point to a number of urgently needed strategies for the FiF cohort to achieve professional goals.